THE INFLUENCE OF TAX EXPENSE AND PROFITABILITY ON TRANSFER PRICING IN MANUFACTURING COMPANIES IN THE CONSUMER GOODS INDUSTRY SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2016 TO 2020 - Anselmus Rufus Kodu; Rimi Gusliana Mais (Bajang Institute, 2024)
This study aims to investigate the influence of tax expense and profitability on transfer pricing decisions in manufacturing companies within the consumer goods industry sector listed on the Indonesia Stock Exchange during the period 2016-2020. Utilizing a quantitative approach and secondary data from annual financial reports, multiple linear regression analysis was conducted to assess the relationship between independent variables (tax expense and profitability) and the dependent variable (transfer pricing). The results indicate that both tax expense and profitability significantly impact firms' transfer pricing decisions. Companies tend to actively employ transfer pricing strategies when faced with high tax expenses and achieve good profitability levels. The implications of this research emphasize the importance of effective transfer pricing management in optimizing tax structures and financial performance, as well as the necessity for clear regulations to ensure compliance and transparency in business practices. This study provides valuable insights for practitioners, academics, and policymakers in comprehending the complexities of transfer pricing within the context of manufacturing companies, while also suggesting further research into more advanced measurement methods related to transfer pricing